Analisis Perubahan coulomb stress Gempa Bumi Cianjur 21 November 2022 - Harefa, Faradilla Firdani; Lubis, Lailatul Husna; Sirait, Ratni (Jurnal Geofisika, 2024)
The earthquake that occurred in Cianjur Regency on November 21, 2022 with a magnitude of 5.6 Mw had a huge impact, including casualties and meterial damage. The location of the earthquake based on data sourced from BMKG was at -6.870° N and 107.016° E and the earthquake occurred due to the Cugenang fault. After the 5.6 Mw earthquake was followed by a series of aftershocks. The purpose of this study was to determine the effect of coulomb stress changes on the Cianjur earthquake and the direction of aftershock distribution using the coulomb stress method. The results of this study show the effect of coulomb stress on earthquakes in Cianjur Regency forming 8 lobes. 4 red lobes that mean an increase in stress, namely (north direction is in Cipanas and Pacet sub-districts, east direction is in Cugenang sub-district, south direction is in Cireunghas sub-district, and southwest to west direction is in Cikole sub-district) with a value of 0 to 0, 2 bar and 4 blue lobes indicating a decrease in stress, namely (northeast direction in Sukaresmi sub-district, southeast direction in Warungkondang, Cibeber and Cilaku sub-districts, southwest direction in Sukaraja, Sukabumi and Sukalarang sub-districts, and west to northwest direction in Nagrak, Kadudampit and Caringin sub-districts) with a value of 0 to -0.2 bar. The distribution of aftershocks was more in Cugenang sub-district and partly in Warungkondang sub-district.